2018
DOI: 10.1166/jnn.2018.14592
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Silver Nano-Particles by Use of Edible Oils

Abstract: Avoiding use of environmentally hazardous reducing agents and surfactants like sodium borohydride, hydrazine hydrate, alkyl amines and alkyl phosphines, the current article describes successful synthesis of silver nanoparticles via green synthesis by employing coconut, Indian gooseberry (amla), almond and mustard oils as capping as well as reducing agents. The presence of various fatty acids in such edible oils act as capping agents through their carboxylic acid functionality and control the growth of nanopart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Therefore alternative strategies to antibiotics are urgently required. While the antibacterial potential of AgNPs has been described ( Morones et al, 2005 ; Li et al, 2011 ; El-Rab, 2012 ; Taglietti et al, 2012 ; Polivkova et al, 2017 ; Saratale et al, 2017 ; Burduşel et al, 2018 ; Kshirsagar et al, 2018 ; Souza et al, 2018 ; Zheng et al, 2018 ; Zhu et al, 2018 ; Some et al, 2019 ), we are unaware of any studies which have examined the antibacterial potential including antibiotic synergistic effects, of biocompatible concentrations of AgNPs. In vitro studies that have assessed the cytotoxicity of AgNPs were either too short, e.g., 24 h or ≤5 days and/or did not consider the antibacterial efficacy ( Patra and Baek, 2017 ; Alsammarraie et al, 2018 ; Botha et al, 2019 ; Samuel et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore alternative strategies to antibiotics are urgently required. While the antibacterial potential of AgNPs has been described ( Morones et al, 2005 ; Li et al, 2011 ; El-Rab, 2012 ; Taglietti et al, 2012 ; Polivkova et al, 2017 ; Saratale et al, 2017 ; Burduşel et al, 2018 ; Kshirsagar et al, 2018 ; Souza et al, 2018 ; Zheng et al, 2018 ; Zhu et al, 2018 ; Some et al, 2019 ), we are unaware of any studies which have examined the antibacterial potential including antibiotic synergistic effects, of biocompatible concentrations of AgNPs. In vitro studies that have assessed the cytotoxicity of AgNPs were either too short, e.g., 24 h or ≤5 days and/or did not consider the antibacterial efficacy ( Patra and Baek, 2017 ; Alsammarraie et al, 2018 ; Botha et al, 2019 ; Samuel et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study we extended these observations to show that at low AgNPs concentrations, i.e., 1.0 μg/mL, the viability of primary human fibroblasts was over 80% even after 7 days of direct culture with the AgNPs. The precise concentration at which AgNPs may be cytotoxic is still unresolved in the literature, primarily due to the wide range of differing methodologies used to produce the nanoparticles and the subsequent in vitro testing systems utilized ( Pan et al, 2007 ; Gaiser et al, 2013 ; Niska et al, 2016 ; Nakkala et al, 2017 ; Kshirsagar et al, 2018 ; Shi et al, 2018 ). At the biocompatible concentration used in this study, Krajewski et al (2013) showed AgNPs did not induce any hematologic changes whereas 3 μg/mL significantly increased CD11b expression on granulocytes while 30 μg/mL induced hemolysis of erythrocytes, α-granule secretion in platelets as well as activation of the coagulation and complement cascades ( Krajewski et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The signature of UV-vis absorption characteristics is observed and the bandgap is calculated to be 2.6 eV and 2.4 eV for P Au -CQD/TiO 2 and P Ag -CQD/TiO 2 NCs, respectively, which is in line with the surface plasmon resonance peaks associated with Au and Ag nanoparticles. 47,48 In addition, the SEM micrographs represent the brous nature of TiO 2 nano-bers, which were used to load P Ag -CQDs and P Au -CQDs for the photocatalytic degradation study of organic pollutants (ESI Fig. S2 †).…”
Section: A Characterization Of P M -Cqd/tio 2 -Based Nanocompositesmentioning
confidence: 99%
“…In green chemistry processes, diverse natural products can be used, from unsaturated fatty acids, peptides, polysaccharides to herbal extracts, among others. [4,12,13,[24][25][26][27] One of the most used polysaccharides is starch, because it is ubiquitous in nature, cheap, biodegradable and biocompatible, easy to acquire, and well-known supramolecular structure and physicochemical properties. [12,13,[26][27][28][29][30][31][32] In the present work, the capping selected to stabilize the Ag-NPs was potato starch.…”
Section: Introductionmentioning
confidence: 99%